Characterization of the alternative splicing regulating the proapoptotic gene BIM. - Lee, Qing Feng. (2012)
Alternative splicing, regulated by cis-acting elements and trans-acting factors, enables the exons of the RNA produced by transcription of a gene to be reconnected in several ways, resulting in different mRNAs being produced. BCL2-homology domain 3 (BH3), essential for proapoptotic function of BIM, is included or excluded from the final BIM protein by means of alternative splicing and it is encoded in Exon 4. Therefore we hypothesized that BIM Exon 4 contains cis-acting elements - Exonic Splicing Enhancers (ESEs) or Exonic Splicing Silencers (ESSs) - , which activate or repress splicing of BIM Exon 4 respectively. Eight-nucleotide serial deletions were introduced to a chimeric BIM minigene to investigate on the presence of cis-acting elements in BIM Exon 4. All wild-type and mutated BIM minigenes resulted in 100% inclusion of Exon 4. These results could be explained by: (i) there is more than one ESE in Exon 4; (ii) alternative splicing of Exon 4 is governed by cis-acting elements in flanking intron regions; (iii) a hybrid environment was unable to replicate alternative splicing of Exon 4 in endogenous context. Additional studies are required to validate our current results and identify cis-acting elements that might govern alternative splicing of BIM Exon 4.